Resource, Environment and Energy Considerations for Maine Food Security in 2050 and Beyond - Beal, Amanda; Jemison, John (Maine Policy Review, 2011)
This article discusses some of the expensive “externalities” produced by industrial agriculture and fishing. These include impaired watershed quality, soil degradation, pollution, reduction in biodiversity, and impacts on human health. The article also includes a discussion of transgenic crops and how these relate to sustainable agriculture